Дослідження технології розробки ігрових додатків з використанням VR - Проценко, В. П. (ХНУРЕ, 2021)
The given work is devoted to the modern development of game supplements for VR victories. To reach the point, it is necessary to have a sense of intelligence, as well as a virtual reality, to look at the type of virtual reality, an intelligence as the very technology of practicality, as annexes are needed for the victorious. Virtual reality is a world created by technical means and transmitted to man through his senses. To create a onvincing set of sensations of reality, a computer synthesis of the properties of virtual reality reactions is performed in real time.
Keywords: ігрові додатки